Liberation of acrylates from nickelalactones via Ni─O ring opening with alkyl iodides. (25th August 2016) - Zhang, Zhizhi; Guo, Fangjie; Kühn, Fritz E.; Sun, Jing; Zhou, Mingdong; Fang, Xiangchen
Abstract : The utilization ofcarbon dioxide as a feedstock for the production of raw chemicals is of high current industrial interest. One attractive reaction is the transformation ofcarbon dioxide into acrylic acid or acrylates. The cleavage of the Ni─O bond of nickelalactones may result in the formation of acrylates. In this work, C2 H5 I, CF3 CH2 I and CF3 I are studied asalkylation reagents for the Ni─Oring opening of nickelalactones. The results indicate that both C2 H5 I and CF3 CH2 I are able to release acrylates from nickelalactones. Based on the experimental evidence and literature precedents, a mechanism – proceeding via Ni─Oring opening of nickelalactone, β‐H elimination to release the acrylate and reductive elimination for recovery of the Ni(0) species – is proposed. Abstract : C2 H5 I and CF3 CH2 I are able to induce the cleavage of Ni─O bond of nickelalactones, affording ethyl acrylate or 2, 2, 2‐trifluoroethyl acrylate as the ring‐opening products.